2013
DOI: 10.3390/ijms141223774
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Smad7 in the Control of Cancer Growth and Metastasis

Abstract: Smad7 was initially identified as an inhibitor of Transforming growth factor (TGF)-β due mainly to its ability to bind TGF-β receptor type I and prevent TGF-β-associated Smad signaling. More recently, it has been demonstrated that Smad7 can interact with other intracellular proteins and regulate also TGF-β-independent signaling pathways thus making a valid contribution to the neoplastic processes in various organs. In particular, data emerging from experimental studies indicate that Smad7 may differently modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 77 publications
4
59
0
1
Order By: Relevance
“…The results showed that miR-497 was significantly downregulated in breast cancer tissues compared with normal tissues, which was consistent with the Dan Li's findings (Li et al, 2011). As an inhibitor of TGF-b signaling, SMAD7 was overexpressed in numerous cancers and its abundance was positively associated with the cancer malignancy (Ekman et al, 2012;Stolfi et al, 2013). Nevertheless, in breast cancer, studies revealed that SMAD7 could exert both anti-and protumor effects.…”
Section: )supporting
confidence: 91%
“…The results showed that miR-497 was significantly downregulated in breast cancer tissues compared with normal tissues, which was consistent with the Dan Li's findings (Li et al, 2011). As an inhibitor of TGF-b signaling, SMAD7 was overexpressed in numerous cancers and its abundance was positively associated with the cancer malignancy (Ekman et al, 2012;Stolfi et al, 2013). Nevertheless, in breast cancer, studies revealed that SMAD7 could exert both anti-and protumor effects.…”
Section: )supporting
confidence: 91%
“…As predicted, depletion of PAR2 but not PAR1 led to either a loss or at least a strong decrease in the responsiveness of the tested genes to TGF-β1 stimulation in all three cell lines (Figure 2A). PAR2 depletion in Panc-1 cells also resulted to a failure of TGF-β1 to induce the expression of factors involved in positive (GADD45b [31, 32]) and negative (Smad7 [33]) feedback regulation of Smad signalling (Figure 2B). These results provide another example of the importance of PAR2 expression for proper regulation of a wide variety of individual TGF-β target genes and provide a molecular explanation for the crucial role of PAR2 in TGF-β -induced migration and invasion (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Smad7-dependent activation of TGFβ signaling is able to induce the epithelial to mesenchymal transition (EMT) in CRC, allowing CRC cells to leave the tissue parenchyma and enter systemic circulation, followed by tumor invasion and metastasis [10]. Smad7 is an inhibitory Smad protein that interacts with TGFβ type I receptor, targeting it for proteasomal degradation and thereby inhibiting TGFβ-I-induced phosphorylation of Smad2/Smad3 [11].…”
Section: Introductionmentioning
confidence: 99%